KEBIJAKAN LUAR NEGERI VIETNAM TERHADAP PERDAGANGAN ANAK VIETNAM DI INGGRIS PERIODE 2017-2021 - Fitriyanti, Rahmi; Salsabila, Ridzky Farah (Emerald: Journal of Economics and Social Sciences, 2023)
This article analyzes Vietnam's foreign policy towards Vietnamese child trafficking in the UK for the 2017-2021 period. There are two aspects studied. The first aspect of the issue of child trafficking that occurs in the UK, the process starts from Vietnam until it crosses the UK border. The second aspect analyzes the loss of life incident which shocked the international mass media. The analysis begins with Vietnam's foreign policy response to its population who are illegal workers and Britain's attitude in trying to anticipate the exploitation of human trafficking. The conceptual framework refers to the concepts of national interests and human security. The findings show that Vietnamese children are often targeted by perpetrators who cheat them out of work opportunities, but in reality they are exploited and sold to brothels to become sex workers in various countries, including the UK. To prevent this, Vietnam ratified the policy of the National Program for the Prevention and Eradication of Human Trafficking, established a Steering Committee for the Prevention and Eradication of Crime, implemented international cooperation in preventing and controlling human trafficking, and established an interdisciplinary working body. group and Steering Committee 138 coordinate with UN-ACT and related bodies in the UK. On the other hand, the UK is trying to collaborate with ECPAT.